(untitled) (Research, Society and Development, 2022)
Introduction: After the detection of SARS-CoV-2 in the city of Wuhan, China, the World Health Organization (WHO) recognized the new Coronavirus infection as a serious public health problem and in March 2020 characterized it as a pandemic. Given this situation, some population groups were considered at high risk for severe cases of Covid-19, including patients with Diabetes mellitus, a clinical condition of high prevalence in the world population. Objective: This study analyzed how the new Coronavirus pandemic affected adult and elderly patients with diabetes mellitus and whether the literature was able to observe the difference in outcomes according to the control measures adopted in each country. Method: A literature review was carried out from the electronic databases PubMed, Virtual Health Library (VHL) and Google Scholar using the keywords “Diabetes mellitus”, “Covid-19”, “Sars Cov 2”, “Coronavirus”, “Adults”. Results: There were 19 studies included in this review. It was observed that diabetes is an important risk factor for Covid-19, with a higher probability of severe disease with the need for invasive mechanical ventilation and higher mortality. The strict and structured confinement had less impact on glycemic control, whereas in countries that did not adopt it, it was possible to observe a deterioration in the glycemic control of patients. Conclusion: Patients with diabetes, especially those with poor glycemic control, are more exposed to the most serious complications of Covid-19. Adequate compliance with social isolation measures was a protective factor for good glycemic control.